The analytical state of the regulatory-legal base of Ukraine on marine mammals - Марінічева, К. В.; Зубрицький, Д. О.; Пчелінська, Л. В. (Scientific Progress & Innovations, 2018)
The study and analysis of the state of the legislative base of Ukraine concerning marine mammals is conducted in this article. The regulatory-legal base as to marine mammals in foreign countries is considered for comparison. The world's leading countries are actively using marine mammals for their fleets, as well as private dolphinariums-oceanariums for ecological-educational activities and show programs. Marine mammals in Ukraine are protected by law and they are the object of monitoring in order to identify the main causes of death, health condition, and reproduction problems. The urgency of the topic is based on the fact that the existing control of illegal or accidental extraction, the death of marine animals in Ukraine is insufficient. Every year a large number of marine mammals (dolphins) die from fishing nets of poachers, under screws bolts of various floating crafts and other kinds of human economic activities (catching fish and seafood, mineral resources, etc.). The introduction of moratorium on the cetaceans’ catching in the Black Sea and Azov Sea for any purpose was due to the deterioration of the situation of protecting marine mammals that are under the danger of extinction. The problem of the mass death of marine mammals is catastrophic. The conclusions and suggestions for solving problematic issues of protecting and preserving marine mammals of the Black Sea are presented. The prospective direction of further research is indicated – the organization of monitoring marine mammals in the system of state ecological monitoring (collecting the data on spreading, including the registration of mammals, cast ashore).